RANCANG BANGUN PROTOTYPE SISTEM KEAMANAN SEPEDA MOTOR BERBASIS E-SIM MENGGUNAKAN RFID - Nur Faqih, Mochamad; Budiyono, Budiyono; Prasetyo, Imam (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2022)
The case of motorcycle theft is not a new or common thing in the ears of the public and the world of the Indonesian National Police or the Indonesian National Police. Motorcycle theft cases can happen at any time. In accordance with the regulations of the Indonesian National Police as stated in Article 18 Paragraph 1 of Law no. 14 of 1992 which reads "Every driver of a motorized vehicle is required to have a driving license." In Indonesia, many minors are not yet ready to ride a motorcycle and do not have a driver's license (SIM). To anticipate the breaking of ignition keys by unscrupulous motorcycle thieves, and comply with the rules from the Police in accordance with Article 18 Paragraph 1 of Law no. 14 Years Old, a motorcycle security system was designed using an e-SIM based on Radio Frequency Identification (RFID). The Radio Frequency Identification (RFID) key also uses an e-SIM and ID tag card as an identity card or identification when trying to turn on or turn off a motorcycle engine. The performance of this card is also supported by the Arduino Nano Microcontroller and Relay. In designing this tool, we connect the cables according to the existing circuit in the security module (Design Tool consisting of Arduino Nano hardware, RFID reader, relay and I/O/I switch) with a skun cable with input and output switches on the motorcycles so that during assembly or experimentation they can be directly connected to the ignition, starter and brake switches to connect the tools designed with automatic motorcycles. To use this tool, it is carried out in three stages (scan) using an e-SIM and ID tag card to turn the motorcycle engine on and off. The first scan, to turn on the motorcycle's electricity. The second scan, to start the motorcycle engineKeywords: e-SIM, RFID, Arduino Nano, Relay